Communication experiences of family caregivers of hospitalized adults with intellectual and developmental disabilities-A qualitative study - Marie Lourdes Charles (Wiley, 2020)
Abstract Aim To explore communication experiences between family caregivers of adults with intellectual and developmental disabilities (I/DD) and healthcare personnel during hospitalization. Design A qualitative descriptive study approach with interviews of family caregivers was used. Method Face‐to‐face, semi‐structured interviews were conducted from June-September 2015 with ten family caregivers of adults with I/DD. Participants were recruited through an advocacy organization in the north‐eastern United States. Data were analysed by content analysis. The Standards for Reporting Qualitative Research was the chosen checklist. Results The four overarching themes: "Need for Advocacy"; "Need for Better Communication"; "Sense of Abandonment"; and "Lack of Confidence" along with 12 subthemes were identified. Overall, participants reported miscommunications leading to instances of mistrust in hospital staff's competence to deliver quality patient care.